Trends in SSRI use in Iceland with a focus on concomitant opioid use and comorbidity - Nicolai Mohr Vang 1990- (2021)
The opioid epidemic that started in the US in the 1990s has since become a global phenomenon. The misuse of opioids as a medicine has become more pronounced, as long-term use of opioids is more prevalent than before, despite clinical guidelines to the contrary. Furthermore, the population is becoming more diseased, and polypharmacy is becoming more common, which calls for more awareness of patients on concomitant use of opioids and other medications. In this study, we have focused on the concomitant use of opioids with SSRIs. Pain and depression have been linked together both sociologically and neurologically. Our data showed a significant increase in the use of SSRIs (+27.3 DDDs per year, 95% CI: +8.7 +46.0) among patients that also redeem over 112 DDDs of opioids per year compared to non-opioid users. Contrastingly, low opioid use (1-28 DDDs per year) was linked to a significant decrease in SSRI use compared to non-opioid users. SSRI use was found to be affected by opioid use and was dose dependant. Low opioid users used fewer DDDs of SSRIs than non-opioid users, and high opioid users used more than non-opioid users. Prevalent opioid use resulted in decreased SSRI use (-94 DDDs per year 95% CI: -104.8 -84.5) when also correcting for interactions between benzodiazepines, Z drugs and opioids. High opioid use was found to interact significantly with any use of benzodiazepine and benzodiazepine related drugs. Although a relationship can be seen between opioid and SSRI use, it is not perspicuous and should be better studied. Opioid users' SSRI dose progression differed considerably compared to non-opioid users, with non-opioid users remaining on a more stable treatment throughout the study period. Comorbidities did not cause a significant increase, except for those suffering over eight chronic conditions. Ópíóíðafaraldurinn sem hófst í Bandaríkjunum á níunda áratugnum hefur breiðst út til annara landa, og orðið að heimsfaraldri. Notkun ópíóíða er oft ekki samkvæmt klínískum leiðbeiningum, sem segja meðferð ...